Effect of Egg‐Replacer and Composite Flour on Physical Properties, Color, Texture and Rheology, Nutritional and Sensory Profile of Cakes. Issue 5 (18th September 2016) - Agrahar‐Murugkar, Dipika; Zaidi, Aiman; Kotwaliwale, Nachiket; Gupta, Chetan
Abstract: Eggless cakes were developed using composite flour (CF) of wheat, malted finger‐millet, sprouted soy and amaranth and egg‐replacers (banana (T1), chia (T2) and soy milk powder (T3)) and were analyzed for physical, textural, rheological, nutritional and organoleptic properties and compared with egg cakes with refined wheat flour (C1) and CF (C2). T1 cake showed no significant difference for batter physical and textural properties with C1. In rheological studies, no significant difference was found for Casson‐plastic viscosity, flow‐behavior index and consistency‐index among T1 and C1 batter. T1 cake had higher volume (437.1 cm 3 ) as compared to T3 (404.4 cm 3 ) and T2 (359.4 cm 3 ). C2 showed highest protein (g/100 g) (14.3) and fat (27), while T3 and T1 cakes contained significantly higher iron contents. On 9‐point hedonic scale, T1 cake scored significantly higher values among T cakes. Therefore, CF was a good replacement for refined flour and banana was the best egg‐replacer for cake developed. Practical Applications: Increasing consumer search for healthier food options has led researchers to look for alternatives of traditional bakery items such as eggs, refined wheat flour, and butter in food products. Refined wheat flour with low gluten, eggs with its unique foaming, emulsifying and heat coagulation properties and butter giving tenderness, moistness and flavor are important ingredients in bakery products especially in cakes and thus difficult to replace by any other source. Therefore, our research on different egg‐replacers and incorporation of composite flour containing whole wheat, sprouted soybean, malted millet and pseudocereals instead of refined wheat flour in cakes may help manufacturers to produce a healthy product with no sacrifice for its taste and appearance. These alternatives deliver same functional role as that of eggs, butter and flour at much lower cost and can be incorporated into the cakes to obtain desirable organoleptic properties.